Epidemiology of Trypanosoma evansi infection in crossbred dairy cattle in Malaysia - Cheah, T.S.; Sani, R.A.; Chandrawathani, P.; Bahri, Sansul (Springer Netherlands, 1999)
An investigation into the epidemiology of Trypansoma evansi infection in crossbred dairy cattle was conducted for a period of 12 months on a dairy cattle farm in Penninsular Malaysia. The prevalence of parasitaemia was highest in lactating animals (13.4%), followed by those in the dry herd (8.8%), late pregnant animals (8.1%), early pregnant animals (4.7%), calves (0.3%) and heifers (0.2%). The prevalence of antigenaemia was highest in the lactating animals (54.7%), followed by that in dry animals (53.7%), heifers (51.1%), late pregnant animals (47.7%), early pregnant animals (46.5%) and calves (24.2%).